1991
DOI: 10.1111/j.1476-5381.1991.tb09789.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐leukocyte interaction in adhesion to endothelial cells induced by platelet‐activating factor in vitro

Abstract: 1 Platelet-activating factor (PAF, 10 nM) did not induce platelet adhesion to endothelial cells cultured in monolayer but it induced their adhesion to protein-coated plastic. However, PAF induced a marked platelet adhesion to endothelial cells when polymorphonuclear leukocytes (PMNs) were present. Lyso-PAF had no effect. 2 Phase-contrast microscopic examination showed that single platelets rather than their aggregates adhered to the endothelial cell surface around aggregating and adhering PMNs. 3 Significant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 28 publications
(19 reference statements)
0
17
0
Order By: Relevance
“…In a previous paper, we demonstrated that PAF induced platelet adhesion to endothelial cell surfaces only in the presence of PMNs in vitro (Hirafuji & Shinoda, 1991a). In the present study, to determine whether PMNs release or generate any factor(s) capable of inducing platelet adhesion, the effects of various cell-free preparations from PMNs on platelet adhesion were first examined.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…In a previous paper, we demonstrated that PAF induced platelet adhesion to endothelial cell surfaces only in the presence of PMNs in vitro (Hirafuji & Shinoda, 1991a). In the present study, to determine whether PMNs release or generate any factor(s) capable of inducing platelet adhesion, the effects of various cell-free preparations from PMNs on platelet adhesion were first examined.…”
Section: Discussionmentioning
confidence: 85%
“…Endothelial cells, platelets and PMNs were prepared as described previously (Hirafuji & Shinoda, 1991a). In brief, endothelial cells were isolated from human umbilical cord veins by collagenase digestion.…”
Section: Methods Endothelial Cells Platelets and Pmnsmentioning
confidence: 99%
See 2 more Smart Citations
“…It also induces adhesion of platelets to the endothelium in the presence of activated leukocytes (Hirafuji and Shinoda, 1991). PAF is also known to play an important role in various pathophysiological conditions that include modulation of blood pressure, hypotension, cardiac dysfunction, cardiac anaphylaxis, hemorrhagic, traumatic and septic shock syndromes (Anderson et al, 1991;Montrucchio et al, 2000).…”
Section: Introductionmentioning
confidence: 99%